Penerapan Manajemen Pendidikan dalam Memperkuat Karakter Siswa di Sekolah - Siti Zuliani; Saidatul Munawaroh (At Tadbir: Journal of Islamic Education Management is published by the Islamic Education Management Study Programme, IAI al Urwatul Wutsqo, Jombang, East Java, Indonesia., 2024)
This study aims to analyse the implementation of education management in strengthening students' character at school. Student character is an important aspect in the formation of a person with integrity, responsibility and good moral values. A qualitative method with a case study approach was used in this research. Data were collected using interviews, documentation, and observation. The results of this study show the integration of character education in learning, extracurricular activities, as well as habituation and acculturation activities. In the classroom, character values such as gotong royong, integrity and independence are instilled through active approaches and independent tasks. Extracurricular activities, such as sports, arts, and religion, strengthen religious, independent, and nationalist characters. In addition, habituation through routine (prayer, ceremony, gotong royong), spontaneous (5 S), and exemplary (discipline) activities are also applied to shape students' characters. Overall, SMPN 1 Mojowarno has succeeded in forming students who are intelligent and have good character.